Characterization of IL-22 Bioactivity and IL-22-Positive Cells in Grass Carp Ctenopharyngodon idella - Yang, Yibin; Wang, Junya; Xu, Jiawen; Liu, Qin; Wang, Zixuan; Zhu, Xiaozhen; Ai, Xiaohui; Gao, Qian; Chen, Xinhua; Zou, Jun (Frontiers in Immunology, 2020)
Interleukin (IL)-22 plays an important role in regulating inflammation clearance of infectious pathogens. IL-22 homologues have been discovered in fish but the functions and the sources producing IL-22 have not been fully characterised. In this study, an IL-22 homologue was identified in grass carp and its bioactivities were investigated. The grass carp IL-22 was constitutively expressed in tissues, with the highest expression detected in gills and hindgut. It was upregulated in the spleen after infection with Flavobacterium columnare and grass carp reovirus, and in the primary head kidney and spleen leucocytes stimulated with LPS and IL-34. Conversely, it was downregulated by Th2 cytokines such as IL-4/13B and IL-10. The recombinant IL-22 produced in bacteria showed stimulatory effect on the expression of inflammatory cytokines and STAT3 in the primary head kidney leucocytes and CIK cells. Moreover, the IL-22 positive cells were found to be induced in the hindgut and head kidney 24 h after infection of F. columnare by confocal microscopy using a monoclonal antibody (GC3-22) produced against the recombinant protein. Our data suggest that IL-22 plays an important role in regulating mucosal and systemic immunity against bacterial and viral infection.